El juego cooperativo en el desarrollo de la inteligencia interpersonal en los niños de educación inicial II de la escuela Gabriela Mistral del cantón Chillanes, provincia Bolívar, periodo 2023 - Arteaga Cayambe, Tania Edelina (2023)
Cooperative play in the development of interpersonal intelligence in children of initial education II of the school Gabriela Mistral of Chillanes canton, Bolivar province 2023". The present research work is based on the lack of interpersonal relationships of the children of this institution, which prevents the strengthening of an affective climate among peers, collaboration, communication and empathy, a situation that is intended to be solved through the proposal of cooperative games, since it will achieve the inculcation of values and behaviors essential for the integral development of children, improving their interpersonal relationships. In order to guarantee the reliability of this project, information was acquired from different authors, such as publications, books and the Internet. Similarly, the methodological section was completed, where the types of research, methodologies, techniques and instruments that served as the basis for conducting this research process were discovered. The problem of interpersonal relationships is supported by the statistical analysis obtained through surveys, interviews and observation sheets, whose results led to the conclusion that cooperative games should be implemented as part of the classroom routine, including them in the curricular planning, depending on the teacher's needs. In this way, it will be possible to help children develop social, emotional, linguistic and motor skills. On the other hand, it is important to emphasize that current education demands an integral formation based on values to help in the construction of the personality and to ensure educational success in the coming years.